Produção e qualidade de sementes de cultivares de soja trânsgenica (CP4-EPSPS, CRY1AC) - Ferreira, Thaís Francielle (2020)
Through the insertion of new genes by transgenics, the intrinsic factors, such as genotype, physiology and chemical composition, can be modified in order to be accentuated and their interaction with the extrinsic factors can be altered, greatly influencing the production and quality of the seeds. Thus, the ain was to verify if the cry1Ac protein affects the quality of IPRO soybean seeds in comparison to RR soybean cultivars, evaluating agronomic performance, chemical composition and seed physiology. Seeds of fourteen transgenic soybean (RR and IPRO) cultivars were used.The seed production field was implanted in a climate region classified as Cwa, arranged in randomized blocks with 3 repetitions. Chapter 2, the evaluations of agronomic performance and photosynthetic efficiency were presented: number of pods, number of nodes per plant, weight of 1000 seeds, productivity, plant height, insertion height of the first pods, lodging index, reading the chlorophyll a, b and total chlorophyll apparatus, ratio of chlorophyll a / b, foliar determination of nutrients N, P, K, Ca, Mg, S, Cu, B, Zn, Fe and Mn. The photosynthetic capacity of IPRO cultivars can be affected by the insertion of the Cry1Ac gene, reflecting in the production components: productivity, number of pods and number of nodes. The use of nutrients linked to the photosynthetic process, N, Mg and Mn, by the group of soybean cultivars IPRO is less efficient compared to the group of RR cultivars. Chapter 3, the chemical composition of the seeds produced through centesimal analysis was carried out. Higher levels of protein in the seeds provide greater germination and vigor, in contrast to higher levels of oil. There is a lower incidence of damage by bedbugs in seeds with a high protein concentration and a higher occurrence in seeds with high concentrations of carbohydrates. Chapter 4, seed quality was evaluated by germination, emergence, accelerated aging, electrical conductivity, tetrazolium tests, visual enzymatic analyzes and quantified. Regarding RR cultivars, the insertion of the Cry1Ac gene in IPRO cultivars shows signs of affecting the physiological quality of seeds. There are no differences between the patterns of enzymatic expression of RR and IPRO cultivars.